Frames and arguments on the admission of refugees: an empirically grounded typology - Daniel Drewski; Jürgen Gerhards (Theory and Society, 2024)
Systematic cross-national analyses of political debates on the admission of refugees and asylum seekers require a theoretically coherent and empirically comprehensive typology of frames and arguments used. The paper proposes such a typology of frames and arguments used by governments, opposition parties and social movements in public debates on the admission of refugees. We argue that the collective identity and characteristics of the receiving country on the one hand and refugees' characteristics on the other constitute the key dimensions to which frames in political discourse about the admission of refugees refer. We distinguish between six different frames – economic, cultural, moral, legal, security-related and international – of how the “we” and the “others” can be interpreted. Furthermore, we specify typical arguments associated with the respective frames for or against the admission of refugees. Given that the typology was developed based on a discourse analysis of a very diverse set of countries, including some of the so-called “Global South”, we claim that it can be used to analyze political debates on the admission of refugees in other countries as well and can thus contribute to an accumulation of knowledge.
Keywords: 300; Refugees; Framing; Typology; Collective identity; Othering